2016
DOI: 10.1016/j.jacc.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment With Omecamtiv Mecarbil to Increase Contractility in Acute Heart Failure

Abstract: In patients with AHF, intravenous OM did not meet the primary endpoint of dyspnea improvement, but it was generally well tolerated, it increased systolic ejection time, and it may have improved dyspnea in the high-dose group. (Acute Treatment with Omecamtiv Mecarbil to Increase Contractility in Acute Heart Failure [ATOMIC-AHF]; NCT01300013).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 27 publications
7
163
0
9
Order By: Relevance
“…The results have not yet been published, but they were announced at the European Society for Cardiology Congress 2013 (REF. 86). The primary end point was an improvement in symptoms of dyspnoea.…”
Section: Myosin Modulators In Clinical Trialsmentioning
confidence: 99%
“…The results have not yet been published, but they were announced at the European Society for Cardiology Congress 2013 (REF. 86). The primary end point was an improvement in symptoms of dyspnoea.…”
Section: Myosin Modulators In Clinical Trialsmentioning
confidence: 99%
“…In line with these recommendations, several ongoing and recently completed AHF trials include in‐hospital WHF as a prospectively defined endpoint ( Table 2, 27, 28, 29, 30, 31, 32, 33, 34, 35); this is likely to contribute to its validation and increase physician familiarity with it as a clinical concept, as well as provide data on the effectiveness of interventions in preventing WHF.…”
Section: What Is ‘In‐hospital Worsening Heart Failure’ and How Has Thmentioning
confidence: 97%
“…Improvements in cardiac function were not associated with increased myocardial oxygen consumption when tested on dogs (36). In human studies omecamtivmecarbil showed dose-and concentration-dependent increases in systolic ejection time, stroke volume and ejection fraction (37,38). While the characteristic prolongation of systolic ejection time may be of concern, as long as relaxation is not prolonged and heart rate is not too high, this increased systolic ejection time should be well tolerated (4).…”
Section: Future Directionsmentioning
confidence: 99%